2004
DOI: 10.1097/00006982-200410000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Function After Subconjunctival Injection of Carboplatin in Fibrin Sealant

Abstract: Subconjunctival delivery of carboplatin in fibrin sealant or BSS does not have a toxic effect on retinal function or structure in a non-tumor-bearing rabbit model at the doses used in this study at 3 weeks' follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…However, in 2004, work by Pardue et al again found ERG responses suggestive of inner retinal toxicity but discovered no changes on light microscopy. In this study, subconjunctival carboplatin (12.2 µg/mL in basic salt solution or 25.1 µg/mL in fibrin sealant) in rabbits resulted in decreased b-wave amplitudes beginning at day 2 and resolving by 2 weeks [39]. While not always consistent with histopathologic correlation, the literature suggests carboplatin has a dose-dependent, inner retinal effect measurable by ERG starting at 10 µg in rabbits (equivalent of 5.88 µg/ml), which may be temporary at certain doses.…”
Section: Discussionmentioning
confidence: 73%
“…However, in 2004, work by Pardue et al again found ERG responses suggestive of inner retinal toxicity but discovered no changes on light microscopy. In this study, subconjunctival carboplatin (12.2 µg/mL in basic salt solution or 25.1 µg/mL in fibrin sealant) in rabbits resulted in decreased b-wave amplitudes beginning at day 2 and resolving by 2 weeks [39]. While not always consistent with histopathologic correlation, the literature suggests carboplatin has a dose-dependent, inner retinal effect measurable by ERG starting at 10 µg in rabbits (equivalent of 5.88 µg/ml), which may be temporary at certain doses.…”
Section: Discussionmentioning
confidence: 73%
“…Animal studies suggest a dose-dependent impact of carboplatin on the choroid and retina [50]. This dose dependent toxicity has been further corroborated by ERG findings in animal models [51]–[53] with an inner retina effect measurable by ERG. In humans, retinal toxicity was “dose-limiting” for intracarotid administration of carboplatin (mean 300 mg/m2) for treatment of brain tumors [54].…”
Section: Discussionmentioning
confidence: 70%
“…At 1, 2, and 4 weeks post-injection, ERG recordings were performed, as previously described [17]. Rats were dark-adapted overnight and then prepared under dim red lights.…”
Section: Methodsmentioning
confidence: 99%